Agent-Based Design Patterns Approach And Its Applications For Business-To-Consumer E-Commerce - Al-Shrouf, Faiz Mohammed (2006)
As the use of software agents continues to grow in e-commerce environments, the analysis and design of agents are often done using an approach, called the Agent-Based Role Modeling (ABRM) approach. This approach has some drawbacks such as lack of reusability of agent components and lack of flexibility in dynamic addition of agents in open e-commerce systems. To overcome shortcomings, a more efficient approach in business software engineering, called the Agent Pattern Driven Business Engineering (APDBE) is developed in this thesis to create Business Agent Patterns (BAP), which will be used to document agent-based commerce patterns for business-based systems. Such BAP are: the Dynamic Design Pattern (DynDP), the De-coupler Design Pattern (DecDP), and the Agent Mediator Design Pattern (MedDP).